Concentrations of sex steroids in fluid from human antral follicles are dynamic and characterize transition from follicular recruitment to dominance - Johannsen, Malene Louise; Mamsen, Linn Salto; Zheng, Mengxue; Styrishave, Bjarne; Hay-Schmidt, Anders; Andersen, Claus Yding (Fertility and sterility, 2025)
To study the dynamic changes of the human intrafollicular concentrations of all sex steroid hormones throughout the natural menstrual cycle using liquid chromatography-tandem mass spectrometry. Observational Study. Follicular fluid (FF; n = 50) and granulosa cells (n = 25) were collected from antral (2-10 mm in diameter) and Graafian follicles (>10-18 mm) in 34 patients undergoing ovarian tissue cryopreservation for fertility preservation from 2014 to 2023. FF from preovulatory (n = 16) and ovulatory (n = 50) follicles was donated by 50 women undergoing ovarian stimulation for fertility treatment. Preovulatory samples were aspirated before induction of final maturation of follicles, and ovulatory samples were collected during oocyte retrieval, 36 hours post trigger. Fifty patients underwent in vitro fertilization/intracytoplasmic sperm injection, and 34 underwent fertility preservation. Concentrations of sex steroids and gene expression of key steroidogenic enzymes in human follicles throughout the menstrual cycle. Sex steroid levels were low in small follicles (2-4 mm) and increased with follicular diameter. In the early to midfollicular phase, levels of 17OH-progesterone (700-900 nM), androstenedione (2,000 nM), and testosterone (340 nM) were elevated. In preovulatory follicles, 17OH-progesterone peaked at 5,300 nM, whereas androstenedione and testosterone declined to <100 nM. This decline coincided with increased CYP19A1 expression, resulting in a 17β-estradiol peak (∼8,000 nM) before ovulation. Progesterone remained <100 nM until surging to 20,000 nM at ovulation. Upregulation of HSD3B2 and CYP19A1 suggested a metabolic shift from the Δ5 pathway (favoring 17β-estradiol production) to the Δ4 pathway (favoring progesterone synthesis), corresponding with ovulation. This is the first study to comprehensively map intrafollicular concentrations of all major sex steroids in FF, alongside gene expression of key enzymes in granulosa cells, across the follicular phase of the menstrual cycle using liquid chromatography-tandem mass spectrometry. These findings enhance our understanding of hormonal regulation and the timing mechanisms that govern human follicle development and ovarian function.